Purchase Strategies for Power Retailers Based on the Non-Cooperative Game. (February 2019) - Wang, Jun; Dou, Xun; Guo, Yanmin; Shao, Ping; Zhang, Xin
Abstract: Power retailers can formulate purchase strategies to participate in market competition according to different objectives in the increasingly open environment of the power market. This paper analyzed the influence of their purchasing behavior on the market clearing, formulated a purchase strategy based on full power clearing and a purchase strategy based on the lowest own cost respectively. The purchase strategy based on the non-cooperative game for power retailers is proposed through the simulation of the clearing of ISO (Independent System Operator) on the basic of knowing the information prepared by the adversary. Finally, the game process is elaborated and an example of the purchase strategy is analyzed.